Mujeres en Acción—Women in Action: Race, Gender and Economic Self-Sufficiency in a Worker-Owned Housecleaning Cooperative - Luis Kong (Adult Education Research Conference, 2006)
This paper investigates the experiences of Spanish-speaking Latina immigrants within a worker-owned housecleaning cooperative. Their learning challenges with language, gender, race and class issues in the process of organizing and managing their cooperative business is discussed from a feminist, learning perspective, popular education and community development approaches within immigrant populations.
Keywords: Cooperatives; Latina immigrants; feminist theory; popular education; community organizing; democratic social change